EXPLORING DIGITAL TRANSFORMATION IN PRESERVICE TEACHER EDUCATION IN AFRICA: PROSPECTS, CHALLENGES, AND IMPLICATIONS FOR SUSTAINABLE LIFELONG LEARNING (International Journal of Innovative Technologies in Economy, 2024)
Digital transformation is reshaping pre-service teacher education globally, with significant implications for Africa. This study explores the prospects and challenges of integrating digital technologies into African pre-service teacher education, examining its impact on sustainable lifelong learning. A systematic literature review method was used to analyse research published between 2020 and 2024, identifying key trends, barriers, and opportunities. The findings highlight the potential of digital tools to enhance educational resources, innovative teaching methods, and collaborative learning environments. However, challenges such as inadequate technological infrastructure, digital literacy gaps, and institutional resistance hinder effective implementation. The Technology Acceptance Model (TAM) and the Lifelong Learning Framework provide theoretical underpinnings, offering insights into technology adoption and continuous professional development. This study presents strategic recommendations for policymakers, educational institutions, and stakeholders to address these challenges and leverage digital transformation for improved educational outcomes. The implications for sustainable lifelong learning emphasise the importance of ongoing professional development and adaptability in the evolving educational landscape. By addressing the identified barriers and implementing targeted interventions, Africa can harness the benefits of digital transformation in preservice teacher education, ultimately contributing to developing a more equitable and effective education system.